The pulsationally modulated radial crossover signature of the slowly rotating magnetic B-type star ξ1 CMa. (24th April 2018) - Shultz, M; Kochukhov, O; Wade, G A; Rivinius, Th
Abstract: We report the latest set of spectropolarimetric observations of the magnetic β Cep star ξ 1 CMa. The new observations confirm the long-period model of Shultz et al. (2017 ), who proposed a rotational period of about 30 years and predicted that in 2018 the star should pass through a magnetic null. In perfect agreement with this projection, all longitudinal magnetic field ⟨ Bz ⟩ measurements are close to 0 G. Remarkably, individual Stokes V profiles all display a crossover signature, which is consistent with ⟨ Bz ⟩ ∼ 0 but is not expected when v sin i ∼ 0. The crossover signatures furthermore exhibit pulsationally modulated amplitude and sign variations. We show that these unexpected phenomena can all be explained by a 'radial crossover' effect related to the star's radial pulsations, together with an important deviation of the global field topology from a purely dipolar structure, that we explore via a dipole+quadrupole configuration as the simplest non-dipolar field.